1995
DOI: 10.1139/v95-107
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of polyoxometalates immobilized in ion exchange polymer films

Abstract: Abstract:The polyoxometalate ions P M O , ,~, ,~~, PW~,O,~-, and S~W,,O,;-are incorporated in polymeric ruthenium(II)(vinyl)bipyridine (poly-~u(vbpy),2+) films from aqueous and dioxane-water electrolytes. Despite their large mass the ions exist as freely diffusing species that compensate for up to 30% of the chage in poly~u ( v b~~)~~~. An investigation of the effect of environmental conditions on electrochemical behavior reveals that the first two one-electron reduction waves of s~w,,o,,~-coalesce into a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The current response increased with the increase of the scan rate (Fig. 4c), and similar curves with three pairs of redox peaks were observed at all scan rates, with no obvious distortion [25]. This observation indicates sufficient electron transfer from the PMo 12 cluster to the electrode in all subsequent redox steps.…”
Section: Electrochemical Characterizationsupporting
confidence: 58%
“…The current response increased with the increase of the scan rate (Fig. 4c), and similar curves with three pairs of redox peaks were observed at all scan rates, with no obvious distortion [25]. This observation indicates sufficient electron transfer from the PMo 12 cluster to the electrode in all subsequent redox steps.…”
Section: Electrochemical Characterizationsupporting
confidence: 58%
“…The attachment of the Keggin [XM 12 O 40 ] p - or Dawson [X 2 M 18 O 62 ] q - parent structure has been largely explored: (i) heteropolyanions are adsorbed on carbon electrode, which often involves vigorous oxidation processes resulting in the formation of oxygenated functional group on carbon surface, whose nature and number are difficult to identify and control; (ii) heteropolyanions as a dopant are immobilized into polymer films (e.g., polypyrrole, polyaniline, polythiophene, and their derivatives). However, in some cases, the polymer environment affects the electrochemical behavior and the electrocatalytic properties of the immobilized heteropolyanions. ,,, (iii) Heteropolyanions are electrodeposited on metal electrode. Despite the amount of literature the many methods used for the attachment of heteropolyanions on substrate surface, little study has been reported on how to design a well-organized and structure-controlled molecular assemblies of heteropolyanion, while maintaining and/or enhancing their above beneficial properties. Recently, several composite film containing heteropolyanion modified electrodes have been prepared by several groups. These techniques were shown to be rapid and simple to obtain organized molecular assemblies experimentally with precise control of layer composition and thickness.…”
Section: Introductionmentioning
confidence: 99%
“…5 To take advantage of their specific properties observed in solution, the attachment of such species onto electrode surfaces is of great interest. The attachment of the Keggin [XM 12 O 40 ] por Dawson [X 2 M 18 O 62 ] qparent structure has been largely explored: (i) heteropolyanions are adsorbed on carbon electrode, [6][7][8] which often involves vigorous oxidation processes resulting in the formation of oxygenated functional group on carbon surface, whose nature and number are difficult to identify and control; (ii) heteropolyanions as a dopant are immobilized into polymer films [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (e.g., polypyrrole, polyaniline, polythiophene, and their derivatives). However, in some cases, the polymer environment affects the electrochemical behavior and the electrocatalytic properties of the immobilized heteropolyanions.…”
Section: Introductionmentioning
confidence: 99%
“…The immobilization of catalytically active species onto solid supports can solve the catalyst recovery and recycle. As a result, water-insoluble polyoxotungstates including insoluble bulk materials, 4,8,9 impregnation of homogeneous catalysts onto inert solid supports metal hydroxides 7,[10][11][12][13] and polymers, [14][15][16][17][18][19] have been synthesized. Although the catalysts immobilized on insoluble resins and silica gels are suitable for this purpose, they often result in lower catalytic activity compared with their soluble counterparts.…”
Section: Introductionmentioning
confidence: 99%